Effect of extrusion variables on extrudates properties of water yam flour a response surface analysis - Oke, M.O.; Awonorin, S.; Sanni, Lateef O.; Asiedu, Robert; Aiyedun, P.O. (Wiley, 2013)
Water yam (Dioscorea alata) flour was processed using standard wet milling procedure prior to the extrusion process, which led to the determination of extrudate properties of the flours.A single-screw extruder (DCE 330, NJ) was used in evaluating the extrudate properties, which included torque, mass flow rate, residence time, specific mechanical energy and expansion ratio of the flours from the water yam samples. The effect of extrusion and process variables: feed moisture content, screw speed and barrel temperature on the extruder torque, residence time, mass flow rate, specific mechanical energy and expansion ratio for the variety were determined and predictive models were also developed using response surface methodology. It was observed that changing the feed moisture content, barrel temperature and screw speed significantly (P < 0.05) affected expansion ratio, torque, mass flow rate, residence time and specific mechanical energy of all the extrudates. Increasing the feed moisture content (18–28% db) and screw speed (80–180 rpm) resulted in a substantial decrease in expansion ratio (46.6%), residence time (27.5%) and specific mechanical energy (83.6%); whereas, increasing the screw speed significantly increased the mass flow rate (64.5%) of extrudates. Regression analysis indicated that screw speed and feed moisture content were the major process variables showing significant (P < 0.05) linear, quadratic and interaction influences on mass flow rate, expansion ratio and specific mechanical energy.